Unstable Distal Tibia Fracture Management By Anatomically Contoured Plate With Mipo Technique (Bangladesh Armed Forces Medical Journal, 2024)
Background: Fracture at distal tibia is a notorious fracture and difficult to manage. This fracture can be managed conservatively or operatively. Minimally invasive percutaneous osteosynthesis (MIPO) technique can be applied in distal tibia fracture and it usually provides better outcome. This technique ensures minimal soft tissue damage, preserves periosteum and hematoma of the fracture. As the fracture site is not opened, indirect fracture reduction technique is applied. This study tries to evaluate the outcome of MIPO technique application in distal tibia fracture management.Methods: The study was cross sectional study and was carried out on 20 patients during the period of January 2019 to July 2021 in orthopaedic department of Combined Military Hospital (CMH), Dhaka. During this tenure all patients who fulfilled the inclusion and exclusion criteria was included in the study. All had close fracture. Follow up interval was at 2 weeks then 06 weeks, thereafter at 3 months, 6 month and 12 months' time from the date of operation. Data were collected and evaluated in terms of bony union and postoperative complications.Results: 12 patients i.e. 60% were male and same percentage of patient had fracture at right lower limb. Mode of trauma was mostly road traffic accidents (RTA) and fall from height. 40 years was mean age of the patients. It was 07 weeks mean partial weight bearing time and 14 weeks mean full weight bearing time. Mean radiological union time was seen at 18 weeks. Non union or delayed union did not happen in any case. But ankle stiffness (3/20) was most commonly found postoperative complications.Conclusion: For distal tibia fracture MIPO technique is a better treatment option as it gives good outcome and fewer complications.Bangladesh Armed Forces Med J Vol 56 No (1) June 2023, pp 1-6